Drug errors in anaesthesia: technology, systems and culture - Evley, Rachel S. (2011)
Annually in Britain, iatrogenic harm results in patient deaths, increased morbidity, and millions of pounds spent on additional healthcare. Errors in the administration of drugs have been identified as a leading cause of patient harm in major international reports,1 2 and the literature also suggests that most practicing anaesthetists have experienced at least one drug error.34